Web Application-Based Health Education Effect in Reducing Preoperative Anxiety Among Orthopaedic Surgery Patients: A Systematic Review - Agus Gunawan; Arif Setyo Upoyo (Media Keperawatan Indonesia, 2026)
Preoperative anxiety is highly prevalent among patients undergoing Orthopaedic surgery and is associated with adverse postoperative outcomes, including increased pain, delayed functional recovery, and prolonged hospital stay. Digital and web-based preoperative health education has emerged as a potential strategy to address these challenges; however, evidence regarding its effectiveness remains heterogeneous. This systematic review aimed to synthesize current evidence on the effectiveness of digital and web-based preoperative education interventions in reducing preoperative anxiety and related outcomes among Orthopaedic surgery patients. This review followed PRISMA 2020 guidelines. A thorough search was performed on ScienceDirect, PubMed, Scopus, EBSCOhost, and Wiley Online Library for studies released from January 2020 to September 2025. Eligible studies included randomized controlled trials, feasibility or pilot randomized studies, and trial protocols. The outcomes of interest encompassed preoperative anxiety, pain levels, opioid consumption, functional recovery, and patient satisfaction. Methodological quality was assessed using the Joanna Briggs Institute's critical appraisal tools. Six studies met the inclusion criteria, involving diverse Orthopaedic populations, including elective and trauma surgeries. Interventions varied and included web-based education, digital behavioral programs, and AI-based chatbot support. Several studies reported reductions in preoperative anxiety, although results were heterogeneous. Digital behavioral interventions demonstrated more consistent benefits for postoperative pain and pain catastrophizing, while education-only platforms showed mixed findings. Patient satisfaction was consistently higher in digital intervention groups. Digital preoperative education shows promising potential to reduce anxiety and enhance patient experience in Orthopaedic surgery. However, heterogeneity in interventions and study designs limits generalizability, indicating the need for larger, methodologically robust trials.